1982
DOI: 10.1139/y82-208
|View full text |Cite
|
Sign up to set email alerts
|

Manganese neurotoxicity: a model for free radical mediated neurodegeneration?

Abstract: In man, manganese neurointoxication is characterised in the early phase by behavior reminiscent of that observed in schizophrenia. During chronic manganese intoxication the neuropsychiatric symptoms manifested earlier disappear and are followed by a permanent neurological phase typified by extrapyramidal symptoms similar to those of Parkinson's disease. Study of manganese intoxication in animals may provide important clues towards elucidation of the biochemical defect underlying neuropsychiatric as well as ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(68 citation statements)
references
References 8 publications
5
62
0
1
Order By: Relevance
“…Parallel studies using Mn 2+ -pyrophosphate or a 1000-fold molar excess of MnCl 2 (Mn 2+ ) or MnSO 4 (Mn 2+ ) resulted in no reaction with L-DOPA. However, the time scale of this study was less than 5 sec, whereas Mn 2+ -driven oxidation of catecholamines apparently occurs much slower (Donaldson et al, 1982), as was the case in our studies. In fact, when known amounts of DA were incubated with Mn (Fig.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations
“…Parallel studies using Mn 2+ -pyrophosphate or a 1000-fold molar excess of MnCl 2 (Mn 2+ ) or MnSO 4 (Mn 2+ ) resulted in no reaction with L-DOPA. However, the time scale of this study was less than 5 sec, whereas Mn 2+ -driven oxidation of catecholamines apparently occurs much slower (Donaldson et al, 1982), as was the case in our studies. In fact, when known amounts of DA were incubated with Mn (Fig.…”
Section: Discussionsupporting
confidence: 41%
“…Our results are consistent with previous studies showing that Mn can decrease DA levels. For example, Poirier et al, (1985) and Donaldson et al, (1982) demonstrated that Mn 2+ increases the rate of DA autooxidation in vitro, whereas others have reported that in vivo MnCl 2 treatment resulted in a decrease in striatal DA in rats (Autissier et al, 1982;Tran et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of extensive research efforts, the evidence for such speculations of manganese pro-oxidant activity, based primarily on use of the divalent salt manganese chloride (MnCl 2 ), has been conflicting. Manganese has been implicated in enhancing dopamine auto-oxidation and oxidative nigral [10,[13][14][15], and in inflicting damage similar to that of other mitochondrial toxins such as carbon monoxide and cyanide [16]. In evaluations of the oxidative character of manganese, several groups have attributed accelerated ROS formation to both the divalent and trivalent states of the metal [17,18].…”
Section: •ϫmentioning
confidence: 99%